Penyusunan Kebutuhan Perancangan Mesin Hemodialisis Menggunakan Kansei Engineering Serta Aplikasi QFD dan TRIZ - Siregar, Khawarita; Ginting, Rosnani; Siregar, Ikhsan (Media Teknika, 2017)
Means of public health is a component in accelerating the improvement of public health degree. Hospitals as health facilities have a very strategic role in providing quality services in accordance with established standards and can reach the whole community. One installation that needs improvement is the quality of instalasai Hemodialysis. The number of patients is increasing every year must be accompanied by improvement of quality of service installation. Based on observations, there were some complaints of patients on hemodialysis installation services. This study intends to improve the quality of care in hemodialysis installations by crafting needs hemodialysis machine design using Kansei Engineering, as well as the application of Quality Function Deployment (QFD) and TRIZ. Kansei Engineering is used to ensure that a service fulfills the desired emotional response. Subsequently used QFD to improve customer satisfaction by improving the quality of services installation hemodialysis. Results of QFD point to contradictions, namely repair and maintenance service of the machine with the alert medics and repair and maintenance of the machine with the cleanliness and comfort of installation. The results showed that the installation of Hemodialysis Patients in fact want a friendly atmosphere of doctors, nurses, and the reception clerk and the condition of hemodialysis machines and devices work properly.